2021- أثر البنية التحتية على النمو الاقتصادي لعينة من البلدان المتطورة دراسة قياسية للفترة 2001: The impact of infrastructure on the economic growth of a sample of developed countries Standard study for the period 2001-2021 - لخضاري بولنوار; بن جدو سامي (Journal of North African Economies, 2025)
This study aims to measure the impact of infrastructure on the economic growth of a sample of developed countries for the period (2001-2021). Using panel data models, we found through static analysis that a fixed-effects model is appropriate, and that an increase in Mobile cellular telephone subscriptions, Fixed-telephone, and railway lead to a decrease in GDP per capita growth, and an increase in fixedbroadband subscriptions, air transport, and container port traffic lead to an increase in per capita growth. Not only that, but with regard to the dynamic analysis, the study concluded that the method of estimating the Instrumented variables (IV) is the most appropriate in the study, as it turned out that the parameter of the second difference for the dependent variable is less than one, which means that the model is accepted and important, which is the basic condition for estimating such a kind of models. The increase in both the first difference for fixed-line telephone subscriptions and the first difference for railways led to a decrease in the first difference for per capita growth. The increase in the second difference in the growth of per capita GDP and the first difference in mobile cellular subscriptions and the first difference in air transport, the first difference in the movement of transport in container ports, leads to an increase in the first difference in per capita growth.